Empreendedorismo feminino no Brasil e sua relação com variáveis econômicas e sociais - Oliveira, Renata Rocha de (2017)
The growth of female entrepreneurship is closely linked to the variables that describe women's entrepreneurial reasons, through economics, income, domestic influences such as motherhood, and often by managing their families alone. We sought to describe these variables in a cohesive way and to prove the reasons for entrepreneurial growth. They are: initial entrepreneurial women, GDP, enrollment in early childhood education, entrepreneurs by opportunity and by necessity, level of schooling - ranges 1 to 4, average family per capita income and average income rate, and number of women employed in the formal market of job. This study aims to verify the growth of female entrepreneurship in Brazil, made possible by correlation analysis. From a quantitative analysis, following a qualitative analysis, through economic and social discussions, we use observation of dispersion diagrams, descriptive statistics through measures of central tendency and measures of dispersion, followed by the analysis of this research , The correlation analysis. Based on bibliographical researches of social nature and discussions, this work comes to collaborate, using statistical methods, with the influence of female entrepreneurship in the Brazilian economy and women's decisions to enter the entrepreneurial market. In the same way as providing scientific enrichment quantitatively tested, for the purposes of discussions about entrepreneurs. As a result of this study, we verified the influence of the number of enrollments in kindergarten, the level of schooling - track 1, the average family per capita income and the number of women employed, in the growth of the female entrepreneur. Also, through complementary results, the ratio of the number of women employed in the formal employment market, with pre-school education, with the percentages of entrepreneurs by opportunity and by necessity, was tested in order to enrich and propose future work in this market thematic. Finally, the results came to corroborate discussions about the entrepreneurial woman, in order to make these relations and motives of the entrepreneurial growth of Brazilian women measurable.